A method for determining fluids contact and identifying types of reservoir fluids in the F3-sandstone reservoir, field case study in Libya - Elhaddad, Elnori; Shafter, Boshnaf; Arebi, Abd Alatie; Shawesh, Monieb (Journal of Pure & Applied Sciences, 2021)
This research study focuses on the use of tools for well X05-NC169a in (X field) in Libya. Tools such as reservoir saturation tool and repeat formation tool used in this study. F3-Sand Stone is the main reservoir and has a gross thickness ranging from 130 to 187 feet. The aim of this study is to identify the type of fluid and to determine fluid contacts in the F3 - Sand Stone Reservoir. The study was based on a petro-physical evaluation on the well X05-NC169a by using log data (Gamma Ray Log, Resistivity Log, Neutron Log and Density Log). The Techlog software was used to analyze the log data, while the Surfer software was used for mapping. The results indicate that it has a hydrocarbon and water column. Apart from combining the petro-physical results of well tests ( RFT data and RST) is to define the reservoir fluids type. The fluid contacts changed when the hydrocarbon fluid level decreased. The most dominant Hydrocarbon in the reservoir, according to RFT, RST, and Petro-physics data, is predominantly two phases. Zones of gas and oil.